2018
DOI: 10.1016/j.beproc.2018.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Owner reported sensory impairments affect behavioural signs associated with cognitive decline in dogs

Abstract: To describe the extent of age-related cognitive decline in dogs, information regarding the baseline occurrence of associated behaviours in the general population is necessary. With a seven-item, data driven Age-Related Changes scale, we evaluated the relationship between sensory functions, training, sex, and the occurrence of behavioural signs associated with cognitive decline across the whole adult lifespan. The twofold difference in lifespan between small and large dogs presents challenges for ageing studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 36 publications
3
29
0
Order By: Relevance
“…The wide range of expected lifespans, a natural risk to develop dementia, and an environment shared with humans, has also made dogs a promising model organism in aging research (for a review see [10]). Since laboratory dogs represent a limited sample of the natural genetic and environmental variability found in human populations and companion (or pet) dogs, the latter has gained more popularity in aging research recently [11][12][13][14][15][16][17][18]. Their behavior also differs from that of laboratory dogs [19] in ways that make the companion dog a more ecologically valid model of human aging.…”
Section: Introductionmentioning
confidence: 99%
“…The wide range of expected lifespans, a natural risk to develop dementia, and an environment shared with humans, has also made dogs a promising model organism in aging research (for a review see [10]). Since laboratory dogs represent a limited sample of the natural genetic and environmental variability found in human populations and companion (or pet) dogs, the latter has gained more popularity in aging research recently [11][12][13][14][15][16][17][18]. Their behavior also differs from that of laboratory dogs [19] in ways that make the companion dog a more ecologically valid model of human aging.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, they are among the few model animals, alongside cats, that naturally develop dementia-like symptoms [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Some tests investigating cognitive skills require extensive pre-training before the animals' behavior can be evaluated with the test [10,15]. The administration of test batteries which capture spontaneous behavioral performances can save on both costs, although, like questionnaires, [16] they might not always distinguish clearly between behavioral differences caused by aging of the brain, body, and sensory systems, or be able to determine whether each system is affected [5]. For this reason, in some investigations, dogs were first pre-selected for equal performance based on sensory acuity tasks [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a problem because some studies have revealed that the relationship between age and behaviour is not always linear 22 , 23 , so dog ageing studies which compared only young and aged dogs or analysed the effect of age only with correlations or with linear models, may have led to biased conclusions. Impaired dogs A proportion of aged dogs, especially those considered senior/geriatric could suffer from age-related physical, sensory, or mental impairments which could change their behaviour compared to that of successfully ageing dogs 24 , 25 . Studies assessing behaviours other than cognition rarely make efforts to identify potentially impaired dogs in their sample, even though individuals with severe behavioural deterioration may affect the general age trajectory of a given personality trait.…”
Section: Introductionmentioning
confidence: 99%